Pre-surgical fMRI Localization of the Hand Motor Cortex in Brain Tumors: Comparison Between Finger Tapping Task and a New Visual-Triggered Finger Movement Task - Ciavarro, Marco; Grande, Eleonora; Pavone, Luigi; Bevacqua, Giuseppina; De Angelis, Michelangelo; di Russo, Paolo; Morace, Roberta; Committeri, Giorgia; Grillea, Giovanni; Bartolo, Marcello; Paolini, Sergio; Esposito, Vincenzo (Frontiers in Neurology, 2021)
Introduction: Presurgical mapping is clinically essential in the surgical management of brain tumors to preserve functions. A common technique to localize eloquent areas is functional magnetic resonance imaging (fMRI). In tumors involving peri-rolandic regions, the Finger Tapping Task (FTT) is typically administered to delineate the functional activation of hand-knob area. However, its selectivity may be limited. Thus, here a novel cue-induced fMRI task was tested, the Visual-triggered Finger Movement Task (VFMT), aimed at eliciting a more accurate functional cortical mapping of the hand region compared to FTT. Method: 20 patients with glioma in peri-rolandic regions underwent preoperative mapping performing both FTT and VFMT. The fMRI data were analyzed for surgical procedures. When the craniotomy allowed to expose motor-cortex, the correspondence with intraoperative direct electrical stimulation (DES) was evaluated through sensitivity and specificity (mean sites = 11) calculated as percentage of true-positive and true-negative rate, respectively. Results: Both at group and at single-subject level, differences among the tasks emerged in the functional representation of the hand-knob. Compared to FTT, VFMT showed a well-localized activation within the hand-motor area and a less widespread activation in associative regions. Intraoperative DES confirmed the greater specificity (97%) and sensitivity (100%) of the VFMT in determining motor eloquent areas. Conclusion: The study provides a novel, external-triggered fMRI task for presurgical motor mapping. Compared to the traditional FTT, the new VFMT may have potential implications in clinical fMRI and surgical management due to its focal identification of the hand-knob region and good correspondence to intraoperative DES.